Perception of Environmental Stress Sources in Intensive Care Unit by Student Nurses - Enes BULUT; Dilek CILINGIR; Gül CAKIR OZMEN (Atatürk University, 2021)
Aim: This study was carried out to determine the perceptions of the student nurses who had nursing clinical practice in the intensive care unit about the environmental stress sources in the intensive care unit. Method: The research was done by the participation of 78 students who being educated in nursing department and had nursing clinical practice at intensive care units. To collect data, "Intensive Care Unit Sources of Environmental Stress Scale" and data collection form developed by the researchers were used. Data were analyzed with percentiles, frequency, average and standart deviation values, t test for independent groups and ANOVA tests. Results: 84.6% of the students participating in the research are between the ages of 19-23, 74.4% are female, 96.2% are single and 78.2% are in the fourth grade. 71.8% of the participants had a middle income level, 42.3% of them had nursing clinical practice in the internal medicine intensive care unit and 76.9% of them had not been in the intensive care unit before. In addition, 64.1% of the students want to work in the intensive care unit. According to the results of the study, "fear of death", "hearing the alarm of the heart monitor goes off", "lack of privacy", "fear of AIDS" and "experiencing pain" are the most important sources of environmental stress for students in intensive care units. In addition, it was determined that the perception of environmental stress sources in the intensive care unit was higher among the students in the 24-27 age group, men and students who had nursing clinical practice in the surgical intensive care unit. Conclusion: This study revealed that the perception of environmental stress sources in intensive care unit of nursing students. By this way, required arrangements will be done in nursing curriculum and the students will be educated more comprehensively about intensive care units.